Ti / IrO2-RuO2 coating titanium anode and preparation method and application thereof
By using Ti/IrO2-RuO2 coated titanium anode in the zinc electrostatic accumulation industry, the problem of increasing lead content in cathode zinc sheets caused by the existing lead-based alloy anode is solved, and the effect of reducing energy consumption, improving current efficiency and reducing lead content is achieved.
Patent Information
- Application Number
- CN202510093726.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-21
- Publication Date
- 2025-05-02
AI Technical Summary
The anode used in the existing zinc-electricity industry is mainly lead-based alloy anode, which leads to an increase in the lead content in the cathode zinc sheet and affects the quality of zinc. In addition, lead is a toxic heavy metal and has great harm to human health.
Iridium ruthenium oxide coating was prepared by sol-gel method using Ti/IrO2-RuO2 coated titanium anode to prepare an iridium ruthenium oxide coating to form a two-dimensional structural coating with excellent acid corrosion resistance and oxygen evolution catalytic properties.
During the zinc electrostatic accumulation process, the titanium anode reduces the anode oxygen evolution potential, improves the reaction rate, improves the current efficiency, reduces energy consumption, and reduces the lead content in the cathode zinc sheet, improving the quality of the zinc electrostatic accumulation product.
Smart Images

Figure CN119913574A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of titanium electrodes, and in particular relates to a Ti / IrO2-RuO2 coated titanium anode and a preparation method and application thereof. Background Art
[0002] At present, most of the anodes used in the zinc electrowinning industry are lead-based alloy anodes. Lead will inevitably dissolve during the electrowinning process, and some of it will be adsorbed or deposited on the cathode zinc sheet, increasing the lead content in the cathode zinc sheet and affecting the quality of zinc. In addition, lead is a toxic heavy metal, and excessive deposition in the body can cause great harm to the human body.
[0003] Titanium electrode, as a star material in the field of electrochemistry, has played an important role in the electrolysis industry with its unique advantages and wide application fields since it was invented by H. Beer in the 1960s. This electrode, which is based on titanium and coated with precious metals or precious metal oxides, not only has extremely high corrosion resistance and electrocatalytic activity, but also has many advantages such as dimensional stability, low operating voltage, and long life.
[0004] The corrosion resistance of titanium electrodes enables them to work stably for a long time in harsh electrolytic environments without dissolving like traditional graphite anodes or lead anodes, thus avoiding contamination of the electrolyte and cathode products. This feature makes titanium electrodes widely used in the chlor-alkali industry, electroplating, metal foil production and other fields. At the same time, their high electrocatalytic activity enables titanium electrodes to work at lower voltages, effectively reducing power consumption and improving production efficiency.
[0005] Therefore, how to provide a titanium anode that can be used for zinc electrowinning is a technical problem that those skilled in the art need to solve urgently. Summary of the invention
[0006] In order to solve the above technical problems, the present invention proposes a Ti / IrO2-RuO2 coated titanium anode and a preparation method and application thereof.
[0007] To achieve the above object, the present invention provides the following technical solutions:
[0008] A Ti / IrO2-RuO2 coated titanium anode, comprising a titanium substrate and a metal oxide coating;
[0009] The molar ratio of Ir to Ru in the metal oxide coating is 5:5.
[0010] Beneficial effects: Ruthenium oxide is a relatively stable oxide with excellent electrical conductivity and electrochemical activity, especially excellent oxygen evolution reaction (OER) activity in acidic solutions; iridium oxide has good corrosion resistance and catalytic activity in certain electrochemical reactions (such as oxygen evolution reaction, OER). Ruthenium-iridium catalyst (Ru-Ir) has stability and catalytic activity in reactions such as OER. The present invention adopts a sol-gel method to fully mix iridium and ruthenium substances, obtains an iridium-ruthenium oxide coating after heat treatment, and finally forms a two-dimensional structured ruthenium-iridium oxide coating, which has better acid corrosion resistance and oxygen evolution catalytic performance.
[0011] A method for preparing a Ti / IrO2-RuO2 coated titanium anode comprises the following steps:
[0012] A mixed solution of citric acid and ethylene glycol is added to a mixed solution of ruthenium trichloride and chloroiridic acid, and then water and hydrochloric acid are added dropwise and ultrasonic treatment is performed to obtain a mixed colloidal solution, which is coated on a titanium substrate, dried, and then sintered to obtain the Ti / IrO2-RuO2 coated titanium anode.
[0013] Beneficial effects: In the process of preparing sol-gel, citric acid as a complexing agent can control the concentration of metal ions and play a dispersing role. Ethylene glycol provides -OH groups in the citric acid sol system, acting as a dispersant and solvent. It can also be used as a stabilizer to ensure the stability of the sol. By adjusting the ratio of the two, a sol-gel with high dispersibility and high stability can be prepared to ensure the uniform mixing of elements such as Ir and Ru, and finally obtain a titanium anode coating with uniform composition. Ultrasonic treatment is also to make the solution fully mixed.
[0014] Preferably, the molar ratio of ruthenium trichloride to chloroiridic acid is 5:5.
[0015] Preferably, the mixed solution of ruthenium trichloride and chloroiridic acid is obtained by dissolving ruthenium trichloride and chloroiridic acid in anhydrous ethanol and subjecting the mixture to ultrasonic treatment for 10 minutes.
[0016] Preferably, the mixed solution of citric acid and ethylene glycol is obtained by dissolving citric acid and ethylene glycol in anhydrous ethanol and subjecting the mixture to ultrasonic treatment for 10 minutes;
[0017] In the mixed solution of citric acid and ethylene glycol, the ratio of the added amounts of citric acid, ethylene glycol and anhydrous ethanol is 1 g:5 mL:5 mL.
[0018] Beneficial effects: In the process of preparing sol-gel, citric acid is used as a complexing agent to control the concentration of metal ions and play a dispersing role. Ethylene glycol provides -OH groups in the citric acid sol system, plays a dispersing and solvent role, and can also be used as a stabilizer to ensure the stability of the sol. By adjusting the ratio of the two, a sol-gel with high dispersibility and high stability can be prepared to ensure the uniform mixing of elements such as Ir and Ru, and finally obtain a titanium anode coating with uniform composition. Ultrasonic treatment is also to make the solution fully mixed. After the above conditions are treated, a stable sol-gel can be obtained.
[0019] Preferably, the sintering temperature is 400-500° C. and the sintering time is 10 minutes.
[0020] Beneficial effect: At this temperature, the sol-gel can undergo a rapid oxidation reaction on the anode surface to generate a mixture of iridium oxide and ruthenium oxide.
[0021] Preferably, the coating amount is 1.0-3.0 mg / cm 2 .
[0022] Beneficial effect: The surface of the titanium substrate after acid etching is pockmarked. To ensure the stability and uniformity of the coating, the coating amount within this range can ensure the coating effect. If the coating amount is too much, the surface coating cannot be strongly combined with the titanium substrate, it is easy to fall off, cannot function, and the cost is high.
[0023] Application of a Ti / IrO2-RuO2 coated titanium anode in zinc electrowinning.
[0024] Beneficial effect: The zinc electrowinning process is in a sulfuric acid system where the electrolyte is zinc sulfate solution. 2+ The concentration is 40-60g / L, H + The concentration is 140-200g / L, the anode is a titanium anode and the cathode is an aluminum plate. The anode produces oxygen evolution reaction and the cathode produces Zn 2 + The titanium anode surface coating of the present invention plays a role in catalyzing oxygen evolution, and the prepared coated titanium anode has the performance of reducing the anode oxygen evolution potential and increasing the reaction rate, thereby improving the current efficiency in the zinc electrowinning process and reducing energy consumption.
[0025] Compared with the prior art, the present invention has the following advantages and technical effects:
[0026] The present invention selects Ir and Ru as coating matrix elements to obtain a Ti / IrO2-RuO2 coated titanium anode. The Ti / IrO2-RuO2 coated titanium anode provided by the present invention can be used in zinc electrowinning industry and has good electrochemical performance. Compared with the pyrolysis method, the titanium anode prepared by the sol-gel method in the present invention has finer and more uniform surface grains, finer and more uniform surface cracks, a larger specific surface area, and better electrocatalytic activity. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:
[0028] Figure 1 The XRD patterns of the coated titanium anodes obtained in Example 1 and Comparative Examples 2-8;
[0029] Figure 2 SEM images of the coated titanium electrodes obtained in Example 1 and Comparative Examples 2-8;
[0030] Among them, 1# is comparative example 2; 2# is (Example 1); 3# Ir:Sn=5:5; 4# Ir:Co=5:5 (Comparative Example 4); 5# Ir:Sb=5:5 (Comparative Example 5); 6# Ru:Sn=5:5 (Comparative Example 6); 7# Ru:Co=5:5 (Comparative Example 7); 8# Ru:Sb=5:5 (Comparative Example 8);
[0031] Figure 3 CV curves of the coated titanium electrodes obtained in Example 1 and Comparative Examples 2-8. DETAILED DESCRIPTION
[0032] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0033] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.
[0034] Unless otherwise specified, the raw materials in the examples of the present invention were purchased from commercial sources;
[0035] The titanium substrate is: a TA2 titanium plate with a size of 30 mm × 10 mm × 3 mm. The titanium plate is polished with sandpaper to remove the surface oxide layer, and the polished titanium plate is placed in a 5% Na2CO3 solution at 60°C for 1 hour, and then the alkali-washed titanium plate is rinsed with deionized water and placed in a 10% (mass concentration) oxalic acid solution for etching at a slightly boiling state for 2.5 hours, and finally ultrasonically treated for 10 minutes, fished out and rinsed with deionized water, dried and immersed in anhydrous ethanol for use;
[0036] The hydrochloric acid used was 36-38% hydrochloric acid purchased from Chengdu Kelong Chemical Reagent Factory;
[0037] Ruthenium trichloride (containing 40% Ru) was purchased from Kunming Boxi Metal Materials Co., Ltd.;
[0038] Chloroiridic acid (containing 35% Ir) was purchased from Kunming Boxi Metal Materials Co., Ltd.
[0039] Tin tetrachloride (analytical grade) was purchased from Xilong Chemical Co., Ltd.;
[0040] Cobalt chloride (analytical grade) was purchased from Xilong Chemical Co., Ltd.
[0041] Oxalic acid (analytical grade) was purchased from Xilong Chemical Co., Ltd.
[0042] Unless otherwise specified, the room temperature or normal temperature in the embodiments of the present invention refers to 25±3°C.
[0043] Example 1
[0044] A method for preparing a Ti / IrO2-RuO2 coated titanium anode comprises the following steps:
[0045] (1) 0.00349 g of ruthenium trichloride and 0.00684 g of chloroiridic acid were dissolved in 5 mL of anhydrous ethanol at a Ru / Ir molar ratio of 5:5, and ultrasonically treated for 10 minutes to obtain solution No. 1;
[0046] (2) Dissolve 1 g of citric acid and 5 mL of ethylene glycol in 5 mL of anhydrous ethanol and perform ultrasonic treatment for 10 minutes to obtain solution No. 2;
[0047] (3) Liquid No. 2 was slowly dripped into Liquid No. 1, and stirring was continued. 5 mL of deionized water and 1 mL of hydrochloric acid were added dropwise, and ultrasonication was performed for 4 hours to obtain a brown colloidal solution to obtain a sol-gel coating solution;
[0048] (4) The sol-gel coating liquid was evenly applied to the treated titanium electrode with a brush, with a coating amount of 2 mg / cm 2 , then place it under an infrared lamp for drying, and then sinter it at 450℃ for 10 minutes. Repeat the above steps until all the coating liquid is applied.
[0049] Example 2
[0050] A method for preparing a Ti / IrO2-RuO2 coated titanium anode comprises the following steps:
[0051] (1) 0.00262 g of ruthenium trichloride and 0.00513 g of chloroiridic acid were dissolved in 5 mL of anhydrous ethanol at a Ru / Ir molar ratio of 5:5, and ultrasonically treated for 10 minutes to obtain solution No. 1;
[0052] (2) Dissolve 1 g of citric acid and 5 mL of ethylene glycol in 5 mL of anhydrous ethanol and perform ultrasonic treatment for 10 minutes to obtain solution No. 2;
[0053] (3) Liquid No. 2 was slowly dripped into Liquid No. 1, and stirring was continued. 5 mL of deionized water and 1 mL of hydrochloric acid were added dropwise, and ultrasonication was performed for 4 hours to obtain a brown colloidal solution to obtain a sol-gel coating solution;
[0054] (4) The sol-gel coating liquid was evenly applied to the treated titanium electrode with a brush, with a coating amount of 1.5 mg / cm 2 , then place it under an infrared lamp for drying, and then sinter it at 450℃ for 10 minutes. Repeat the above steps until all the coating liquid is applied.
[0055] Example 3
[0056] A method for preparing a Ti / IrO2-RuO2 coated titanium anode comprises the following steps:
[0057] (1) 0.00522 g of ruthenium trichloride and 0.0103 g of chloroiridic acid were dissolved in 5 mL of anhydrous ethanol at a Ru / Ir molar ratio of 5:5, and ultrasonically treated for 10 minutes to obtain solution No. 1;
[0058] (2) Dissolve 1 g of citric acid and 5 mL of ethylene glycol in 5 mL of anhydrous ethanol and perform ultrasonic treatment for 10 minutes to obtain solution No. 2;
[0059] (3) Liquid No. 2 was slowly dripped into Liquid No. 1, and stirring was continued. 5 mL of deionized water and 1 mL of hydrochloric acid were added dropwise, and ultrasonication was performed for 4 hours to obtain a brown colloidal solution to obtain a sol-gel coating solution;
[0060] (4) The sol-gel coating liquid was evenly applied to the treated titanium electrode with a brush, with a coating amount of 3 mg / cm 2 , then place it under an infrared lamp for drying, and then sinter it at 400℃ for 10 minutes. Repeat the above steps until all the coating liquid is applied.
[0061] Comparative Example 1
[0062] A method for preparing a Ti / IrO2-RuO2 coated titanium anode, which is different from Example 1 in that a thermal decomposition method is used for preparation, and specifically comprises the following steps:
[0063] IrCl3 and RuCl3 were added to a mixed solvent (n-butanol and anhydrous ethanol were mixed in a volume ratio of 1:1) at a Ru / Ir molar ratio of 5:5, and a coating solution was prepared by ultrasonic mixing. The coating solution was evenly applied to the surface of the titanium substrate with a fine-bristled brush, and infrared irradiation was performed for 30 minutes until the coating solution was completely dry. The substrate was then transferred to a muffle furnace and calcined at 450°C for 10 minutes. After natural cooling, the coating solution was applied again, infrared irradiation was performed, and calcination was performed. The above steps were repeated for many times, and the last calcination time was 1 hour. After natural cooling, the electrode preparation was completed, and the coating amount was 2 mg / cm 2 .
[0064] Comparative Example 2
[0065] A method for preparing a Ti / IrO2-RuO2 coated titanium anode is different from that in Example 1 in that the molar ratio of Ru / Ir is 7:3. The remaining process steps and parameters are the same as those in Example 1.
[0066] Comparative Example 3
[0067] A method for preparing a Ti / IrO2-Sb2O3 coated titanium anode, which is different from that of Example 1 in that in step (1), 0.00266 g of antimony trichloride and 0.00474 g of chloroiridic acid are dissolved in 5 mL of anhydrous ethanol at a Sb / Ir molar ratio of 5:5, and ultrasonically treated for 10 minutes to obtain liquid No. 1;
[0068] The remaining process steps and parameters are the same as those in Example 1.
[0069] Comparative Example 4
[0070] A method for preparing a Ti / IrO2-CoO coated titanium anode, which is different from that of Example 1 in that in step (1), 0.00261 g of cobalt chloride and 0.00817 g of chloroiridic acid are dissolved in 5 mL of anhydrous ethanol at a Co / Ir molar ratio of 5:5, and ultrasonically treated for 10 minutes to obtain solution No. 1;
[0071] The remaining process steps and parameters are the same as those in Example 1.
[0072] Comparative Example 5
[0073] A method for preparing a Ti / IrO2-SnO2 coated titanium anode comprises the following steps:
[0074] (1) Dissolve 0.00652 g of chloroiridic acid in 5 mL of anhydrous ethanol and treat with ultrasound for 10 minutes to obtain solution No. 1;
[0075] (2) Dissolve 1 g of citric acid and 5 mL of ethylene glycol in 5 mL of anhydrous ethanol and perform ultrasonic treatment for 10 minutes to obtain solution No. 2;
[0076] (3) Liquid No. 2 was slowly dripped into Liquid No. 1, and 5 mL of deionized water and 1 mL of hydrochloric acid were added dropwise. The mixture was ultrasonicated for 4 hours to obtain a brown colloidal solution, thereby obtaining Liquid No. 3;
[0077] (4) According to the designed coating Ir / Sn molar ratio of 5:5, tin tetrachloride was weighed and dissolved in 5 mL of anhydrous ethanol, ultrasonically treated for 10 minutes, and then 5 mL of deionized water and 1 mL of hydrochloric acid were added, and ultrasonicated for 1 hour to obtain solution No. 4;
[0078] (5) Then, liquid No. 4 is slowly added to liquid No. 3 under ultrasonic conditions for 1 hour, and the mixture is allowed to stand for more than 38 hours to obtain a sol-gel coating solution;
[0079] (6) The sol-gel coating liquid was evenly applied to the treated titanium electrode with a brush, and the coating amount was 2 mg / cm 2 , then place it under an infrared lamp for drying, and then sinter it at 450℃ for 10 minutes. Repeat the above steps until all the coating liquid is applied.
[0080] Comparative Example 6
[0081] A method for preparing a Ti / RuO2-Sb2O3 coated titanium anode, which is different from Example 1 in that in step (1), 0.00294 g of ruthenium trichloride and 0.00323 g of antimony trichloride are dissolved in 10 mL of anhydrous ethanol at a Ru / Sb molar ratio of 5:5, and ultrasonically treated for 10 minutes to obtain liquid No. 1;
[0082] The remaining process steps and parameters are the same as those in Example 1.
[0083] Comparative Example 7
[0084] A method for preparing a Ti / RuO2-CoO coated titanium anode, which is different from that of Example 1 in that in step (1), 0.00599 g of ruthenium trichloride and 0.00375 g of cobalt chloride are dissolved in 10 mL of anhydrous ethanol at a Ru / Co molar ratio of 5:5, and ultrasonically treated for 10 minutes to obtain solution No. 1;
[0085] The remaining process steps and parameters are the same as those in Example 1.
[0086] Comparative Example 8
[0087] A method for preparing a Ti / RuO2-SnO2 coated titanium anode comprises the following steps:
[0088] (1) Dissolve 0.00439 g of ruthenium trichloride in 5 mL of anhydrous ethanol and treat with ultrasound for 10 minutes to obtain solution No. 1;
[0089] (2) Dissolve 1 g of citric acid and 5 mL of ethylene glycol in 5 mL of anhydrous ethanol and perform ultrasonic treatment for 10 minutes to obtain solution No. 2;
[0090] (3) Liquid No. 2 was slowly dripped into Liquid No. 1, and 5 mL of deionized water and 1 mL of hydrochloric acid were added dropwise. The mixture was ultrasonicated for 4 hours to obtain a brown colloidal solution, thereby obtaining Liquid No. 3;
[0091] (4) According to the designed coating Ru / Sn molar ratio of 5:5, tin tetrachloride was weighed and dissolved in 5 mL of anhydrous ethanol, ultrasonically treated for 10 minutes, and then 5 mL of deionized water and 1 mL of hydrochloric acid were added and ultrasonicated for 1 hour to obtain liquid No. 4.
[0092] (5) Then, liquid No. 4 is slowly added to liquid No. 3 under ultrasonic conditions for 1 hour, and the mixture is allowed to stand for more than 38 hours to obtain a sol-gel coating solution;
[0093] (6) The sol-gel coating liquid was evenly applied to the treated titanium electrode with a brush, and the coating amount was 2 mg / cm 2 , then place it under an infrared lamp for drying, and then sinter it at 400-500℃ for 10 minutes, and repeat the above steps until all the coating liquid is applied.
[0094] Application Example 1
[0095] Application of a coated titanium anode in zinc electrowinning comprises the following steps:
[0096] A continuous zinc electroplating experiment of 24 hours was conducted on the titanium anode obtained in Examples 1-3 and Comparative Examples 1-8. The experimental conditions are: the anode is the titanium anode obtained in Examples 1-3 and Comparative Examples 1-8, the cathode is a pure aluminum plate, the electrolyte is a 55g / L Zn2SO4 solution, the electrolyte acidity is H2SO4165g / L, the electrolytic cell temperature is 38°C to 40°C, the electrolysis time is 24h, the electrolyte flow rate is 470mL / h, the cell voltage is low at 2.90V, the current efficiency reaches 90.3%, the DC power consumption is reduced by about 300kW·h / t-Zn compared with the national average level, the quality of electrolytic zinc reaches the national 0# zinc standard, and the lead content is reduced by 2 orders of magnitude compared with the lead-silver alloy anode, which provides a new idea for lead-free electrolysis in the electrolytic zinc industry.
[0097] Technical effect:
[0098] 1.XRD analysis
[0099] Figure 1The XRD patterns of the binary coating titanium anode obtained in Example 1 and Comparative Examples 2-8 are the corresponding standard patterns of Ti (PDF#65-3362), IrO2 (PDF#86-0330), RuO2 (PDF#70-2662), SnO2 (PDF#72-1147), Co3O4 (PDF#76-1802), and SbO2 (PDF#71-0143). Some characteristic peaks in the figure are significantly offset, which indicates that a solid solution is generated in the coating, and the solid solution has the catalytic activity common to several metal oxides. At the same time, the solid solution has good stability, which is conducive to the corrosion resistance and stability of the coating.
[0100] 2. SEM analysis
[0101] Figure 2 The SEM images of the binary coated titanium electrodes obtained in Example 1 and Comparative Examples 2-8 are shown. As can be seen from the figure, the coating surface of Example 1 prepared by the sol-gel method has obvious cracks. This is due to the inconsistent expansion and contraction of different substances during heat treatment. The cracks help to increase the surface area of the coating, increase the catalytic activity potential of the coating, and help improve the performance of the electrode. When the composition of the substance in the coating is changed, the surface morphology of the coating can be significantly changed. When elements such as Sn, Co, and Sb are added to the coating, it can be clearly seen under a scanning electron microscope that the coating surface is evenly distributed with "petal-shaped" and "fish-shaped" crystals when magnified 10,000 times, and the crystal petals formed by different added elements are roughly the same. This may be due to the addition of Sn, Co, Sb and other elements and the formation of solid solution oxide crystals with the main elements Ir and Ru in the coating.
[0102] 3. Cyclic voltammetry curve test
[0103] Figure 3 The CV curves of the binary coated titanium electrodes obtained in Example 1 and Comparative Examples 2-8 are shown in the figure. It can be seen from the figure that the CV curves of the several coatings all fluctuate, indicating that the coatings all have obvious redox reactions during the test and show certain catalytic activity. The sizes of the areas enclosed by the cyclic voltammetry curves of the several coatings are quite different. Generally, the size of the area enclosed by the cyclic voltammetry curve can reflect the amount of catalytic activity potential of the electrode. The area q is obtained by integrating the curve between 0V and 0.75V. (Ir:Ru=3:7) =256.18mC·cm -2 ,q (Ir:Sb=5:5) =203.89mC·cm -2 ,q (Ir:Co=5:5) =216.15mCA·cm -2 ,q (Ir:Sn=5:5) =203.67mC·cm -2 ,q (Ir:Ru=5:5)=533.11mC·cm -2 ,q (Ru:Sb=5:5) =203.89mC·cm -2 ,q (Ru:Co=5:5) =216.15mC·cm -2 ,q (Ru:Sn=5:5) =203.67mC·cm -2 It can be seen that the surface of the titanium anode coated in Example 1 has the most catalytic active sites, and the active potentials of the other coatings are not much different.
[0104] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.
Claims
1. A Ti / IrO2-RuO2 coated titanium anode, characterized in that: including a titanium substrate and a metal oxide coating; The molar ratio of Ir to Ru in the metal oxide coating is 5:
5.
2. The method for preparing a Ti / IrO2-RuO2 coated titanium anode according to claim 1, characterized in that: The following steps are involved: A mixed solution of citric acid and ethylene glycol is added to a mixed solution of ruthenium trichloride and chloroiridic acid, and then water and hydrochloric acid are added dropwise and ultrasonic treatment is performed to obtain a mixed colloidal solution, which is coated on a titanium substrate, dried, and then sintered to obtain the Ti / IrO2-RuO2 coated titanium anode.
3. The method for preparing a Ti / IrO2-RuO2 coated titanium anode according to claim 2, characterized in that: The molar ratio of the ruthenium trichloride to the chloroiridic acid is 5:
5.
4. The method for preparing a Ti / IrO2-RuO2 coated titanium anode according to claim 2, characterized in that: The mixed solution of ruthenium trichloride and chloroiridic acid is obtained by dissolving ruthenium trichloride and chloroiridic acid in anhydrous ethanol and then ultrasonically treating the solution for 10 minutes.
5. The method for preparing a Ti / IrO2-RuO2 coated titanium anode according to claim 2, characterized in that: The mixed solution of citric acid and ethylene glycol is obtained by dissolving citric acid and ethylene glycol in anhydrous ethanol and then ultrasonically treating for 10 minutes; In the mixed solution of citric acid and ethylene glycol, the ratio of the added amounts of citric acid, ethylene glycol and anhydrous ethanol is 1 g:5 mL:5 mL.
6. The method for preparing a Ti / IrO2-RuO2 coated titanium anode according to claim 2, characterized in that: The sintering temperature is 400-500° C. and the sintering time is 10 minutes.
7. The method for preparing a Ti / IrO2-RuO2 coated titanium anode according to claim 2, characterized in that: The coating amount is 1.0-3.0 mg / cm 2 .
8. Use of a Ti / IrO2-RuO2 coated titanium anode as claimed in claim 1 in zinc electrowinning.
Citation Information
Cited By
Preparation of high-activity ruthenium-iridium-titanium membrane electrode by PVA-assisted thermal decomposition-high-temperature roasting method
CN121342165A